Outwitting repression of the media in PNG - Sean Dorney (Asia Pacific Network, 1999)
'Papua New Guinea could possbily teach the rest of the world a thing or two about preserving press freedom. What has worked in the media's favour in PNG is the country's vibrant—you could say rampant— democracy.'